Intersectional Effects of Gender, Education, and Geographic Region on Functional Health Disparities Among Older Adults in India. (October 2020) - Roy, Moushumi; Bhatta, Tirth; Burnette, J. Denise
Objective: Research on social determinants of health in India has focused largely on the independent influence of education, gender, and region. Using an intersectionality framework in this study, we examine the combined effects of these three key social locators on the critical, yet underexamined outcome of later life functional health.Method: We use data from Wave 1 (2007–2010) of the Study of Global Ageing and Adult Health (SAGE) ( N = 7, 150) to examine whether the effects of education on functional limitations differ by gender in six highly heterogenous regions of India.Results: The effects of education on functional limitations were significantly greater (β = .026, p < .001) for men than women. Consistent with established regional differences in economic development, cultural practices, and political context, this relationship varied across locales.Discussion: Our findings highlight the need to move beyond independent sources of heterogeneity in examining later life functional health in the global South.